Selective formation and structural properties of rhombic dodecahedral [70]fullerene microparticles formed by reaction with aliphatic diamines - Matsuoka, Ken-ichi (Langmuir : the ACS journal of surfaces and colloids, 2010)
We have accomplished the selective formation of rhombic dodecahedral microparticles on the submicrometer to micrometer scale by the reaction of [70]fullerene (C(70)) with primary aliphatic diamines. The morphology of the resultant microparticles was analyzed by scanning electron microscopy, powder X-ray diffraction, and other spectroscopic methods, demonstrating that the resultant particles held a rhombic dodecahedral shape having a simple cubic lattice structure and that primary aliphatic amines were mostly trapped inside the particles through electronic interaction between C(70) and amines. Furthermore, we have discovered interesting structural characteristics in which the incorporated amines could be removed from the C(70) microparticles or exchanged with other primary aliphatic diamines